2011
DOI: 10.1021/jp2061305
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Hydrogen-Bonded Complexes Based on 2-Ureido-4[1H]-pyrimidinone: A Theoretical Study

Abstract: In the present work, the electronic structures and properties of a series of 2-ureido-4[1H]-pyrimidinone(UPy)-based monomers and dimers in various environments (vacuum, chloroform, and water) are studied by density functional theoretical methods. Most dimers prefer to form a DDAA-AADD (D, H-bond donor; A, H-bond acceptor) array in both vacuum and solvents. Topological analysis proved that intramolecular and intermolecular hydrogen bonds coexist in the dimers. Frequency and NBO calculations show that all the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 59 publications
2
30
0
Order By: Relevance
“…It is noted that the water contact angle on polymer PBA–UPy7.2 decreased by about 10 degrees after a few minutes due to the overturning or migration of polar UPy groups at the polymer surface. Recent theoretical analysis shows that UPy–UPy binding energy can be reduced from ≈–161 kJ mol −1 in vacuum to –69 kJ mol −1 in water and that the binding energy of interaction between UPy and water molecules is competitive with that of UPy‐UPy . Temperature also has a significant impact on the self‐adhesion of PBA–UPy polymers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that the water contact angle on polymer PBA–UPy7.2 decreased by about 10 degrees after a few minutes due to the overturning or migration of polar UPy groups at the polymer surface. Recent theoretical analysis shows that UPy–UPy binding energy can be reduced from ≈–161 kJ mol −1 in vacuum to –69 kJ mol −1 in water and that the binding energy of interaction between UPy and water molecules is competitive with that of UPy‐UPy . Temperature also has a significant impact on the self‐adhesion of PBA–UPy polymers.…”
Section: Resultsmentioning
confidence: 99%
“…For the PBA–UPy7.2 polymer, its higher T g , longer effective bond lifetime τnormalb* (≈3 vs ≈20 s), lower mobility of its chains and a stronger interaction due to the increased mole fraction of UPy groups make the PBA–UPy7.2 polymer more elastic than the PBA–UPy4.0 polymer and the diffusion of water molecules in the PBA–UPy7.2 film would be relatively more difficult than that for the PBA–UPy4.0 case . Increasing the relative humidity also dramatically increases the density of free UPy functional groups on the surface, and this effect is relatively more significant for PBA–Upy7.2 than for PBA–UPy4.0. The overall effect of relative humidity on the bulk viscoelastic properties (e.g., G′, G″) and surface chemistry ( γ values) of the two PBA–UPy polymers, is to increase their adhesion by ≈50% when increasing the relative humidity from 0% to 100% at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…They investigated the influence of the contact time, temperature and humidity. Although theoretical analysis pointed out that the UPy–UPy binding energy decreases with increasing water content, a higher humidity unexpectedly led to stronger adhesion. Contact angle measurements demonstrated that surface migration of UPy groups was responsible for this.…”
Section: Adhesives Based On Hydrogen Bondingmentioning
confidence: 97%
“…Density functional theory studies of UPy binding indicate that dimerization should not occur in water, although dimerization readily occurs in chloroform. 20 However, UPy association has been observed in water-swollen systems involving microphase segregated environments. For example, the non-polar microenvironments within UPy-containing block copolymer pluronics and aliphatic dendritic dimers promote UPy dimerization.…”
Section: Introductionmentioning
confidence: 99%